2021
DOI: 10.1111/1462-2920.15612
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic potentials of members of the class Acidobacteriia in metal‐contaminated soils revealed by metagenomic analysis

Abstract: The relative abundance of Acidobacteriia correlated positively with the concentrations of arsenic (As), mercury (Hg), chromium (Cr), copper (Cu) and other metals, suggesting their adaptation of the metal-rich environments. Metagenomic binning reconstructed 29 high-quality metagenome-assembled genomes (MAGs) associated with Acidobacteriia, providing an opportunity to study their metabolic potentials. These MAGs contained genes to transform As, Hg and Cr through oxidation, reduction, efflux and demethylation, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(8 citation statements)
references
References 97 publications
0
8
0
Order By: Relevance
“…In contrast, their abundance in tailing and waste rock was very low, indicating that these microorganisms can adapt to low-pH environments ( Figure 6 ). In another study, Acidobacteriae was significantly enriched in acid soil that was severely polluted with heavy metals [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, their abundance in tailing and waste rock was very low, indicating that these microorganisms can adapt to low-pH environments ( Figure 6 ). In another study, Acidobacteriae was significantly enriched in acid soil that was severely polluted with heavy metals [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the relative abundance of Acidobacteria , which was the second most abundant phylum, was suppressed by N and S fertilization, and its function cannot be ignored. Xu et al (2021) suggested that Acidobacteria may resist or transform metal(loid)s in metal-contaminated sites. In this study, the relative abundance of Bacteroidetes was also increased by the application of N and S fertilizers, and Lin et al (2019) reported that Bacteroidetes are the most dominant microbial group in heavy metal-contaminated soil.…”
Section: Discussionmentioning
confidence: 99%
“…However, the relative abundance of Acidobacteria, which was the second most abundant phylum, was suppressed by N and S fertilization, and its function cannot be ignored. Xu et al (2021) suggested that Acidobacteria may resist or transform Structural equational model on the relationship between soil properties ˎmicrobial community and the total absorption of heavy metal.…”
Section: Changes In Dominant and Special Microbesmentioning
confidence: 99%
“…Some members of the Acidobacteriaceae family, isolated from mine waters, have been shown to reduce Fe 3+ [45]. Moreover, Acidobacteriia, the most common class of Acidobacteria in low-pH environments, is composed of well-known metal-tolerant strains able to participate in the redox cycle of a variety of metals and metalloids, such as As, Cr, and Hg [43,46].…”
Section: Discussionmentioning
confidence: 99%